Faith-Based Learning through Play: Developing Islamic Education Methods in Early Childhood Education - Wardani, Anita; Mukhlisah, Iffah; Intan Apriliani, Elina; Jafar Nashir, Muhammad (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2025)
The present study aims to describe faith-based learning strategies through play in the context of Islamic Religious Education (IRE) for early childhood. In addition, the study will identify supporting factors, obstacles, and children's responses to these strategies. The present study employed a descriptive qualitative approach, with five teachers from five different kindergartens selected purposively as participants. The data were collected through a combination of in-depth interviews, participatory observation, and document analysis. These data were then analyzed using Miles and Huberman's interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The findings of the study suggest that educators employ a variety of play-based strategies to instill religious values, including role-playing, creative projects, nature exploration, motor games, and interactive digital media. These strategies are meticulously designed to integrate religious messages into recreational activities, thereby facilitating natural and meaningful learning for children according to their developmental stages. The efficacy of these strategies was influenced by three factors: the creativity of the teaching staff, the availability of learning media, and the active involvement of the children. These findings indicate that faith-based learning through play is a viable methodology for Islamic education in early childhood education. This approach integrates a pedagogical approach that is suitable for children with the inculcation of profound religious values.